Staged oxy-fuel natural gas combined cycle - Khallaghi, Navid; Hanak, Dawid P.; Manovic, Vasilije (Elsevier, 2019)
Exhaust gas recirculation (EGR) in conventional natural gas-fired oxy-combustion cycles is required to maintain the combustion temperature at an allowable level. However, EGR is not beneficial from the system performance perspective. It is difficult to achieve in oxy-fuel cycles due to the high pressure and increased pressure drop in such systems. Consequently, alternative options to control the combustion temperature need to be considered. In this study, staged oxy-fuel natural gas combined cycle (SOF-NGCC) was proposed, which does not require EGR, and its feasibility was evaluated. A process model was developed in Aspen Plus in order to evaluate the thermodynamic performance of the proposed system and to benchmark it against the Allam cycle and conventional NGCC. The optimum net efficiency of the proposed cycle (47.63–51.32%) was shown to be lower than that for Allam cycle (54.58%) and the conventional NGCC without post-combustion capture (PCC) (56.95%). However, the SOF-NGCC is less complex and requires smaller equipment than the Allam cycle. This is mostly because the combined volumetric flow rate into expanders in both topping and bottoming cycles is approximately 25% of that estimated for the Allam cycle. Moreover, with a backpressure of 35 bar, no further compression is required prior to the CO2 purification unit.
Keywords: Supercritical CO2 cycle; staged combustion; exhaust gas recirculation; natural gas; oxy-combustion cycle; Carbon capture